The hygiene hypothesis of crime: Examining the link between disgust-related diseases and crime incidence - Samudera F. Jamaluddin (Acta Psychologica)
Disgust, an evolutionarily adaptive mechanism for pathogen avoidance, plays a critical role in shaping social and moral behaviors. However, its influence on societal outcomes, such as crime, remains underexplored. This study examines the relationship between disgust-related diseases (diarrhea, HIV, and leprosy) and violent crimes (sex-related crimes, assault, and homicide) in Indonesia, a high-pathogen-stress environment. Using publicly available data from 2022 to 2023, we analyzed correlations between disease prevalence and crime incidents, controlling for socioeconomic factors, including population density, the Gini coefficient, the unemployment rate, the Human Development Index (HDI), and a refined divorce ratio in 34 provinces in Indonesia. The findings reveal that disgust-related diseases are consistently associated with elevated crime incidents, even after adjusting for socioeconomic controls. In contrast, vector-related diseases (e.g., malaria, dengue, and filariasis) demonstrate weaker and less consistent associations. Composite measures further indicate that disgust-related diseases are strong predictors of overall crime index. The overall model explain 68.5 % of its variance. These results support the hypothesis that pathogen-related disgust mechanisms uniquely contribute to societal dynamics, extending pathogen avoidance theory to the realm of criminology. This research underscores the intersection of public health and societal stability, highlighting the need for interdisciplinary strategies to address disgust-related diseases and their broader social implications.